THE CONTRIBUTION OF CLASSROOM MANAGEMENT AND TEACHERS’ SOCIAL SUPPORT TO STUDENTS’ ACADEMIC RESILIENCE - Salmiati; Jasiah (World Psychology, 2026)
Academic resilience has become a crucial construct in understanding students’ capacity to persist and adapt in the face of increasing academic demands and learning challenges. Learning environments that are both well managed and socially supportive are assumed to play a vital role in fostering such resilience, yet empirical evidence integrating these factors remains limited. This study aims to examine the contribution of classroom management and teachers’ social support to students’ academic resilience within formal school settings. A quantitative correlational research design was employed, involving students as respondents selected through stratified random sampling. Data were collected using standardized questionnaires measuring classroom management, teachers’ social support, and academic resilience, and were analyzed using descriptive and inferential statistical techniques. The results indicate that both classroom management and teachers’ social support significantly contribute to students’ academic resilience, with teachers’ social support emerging as the stronger predictor. Structured classroom environments and supportive teacher–student relationships were found to jointly enhance students’ persistence, adaptability, and coping strategies when facing academic difficulties. These findings suggest that academic resilience is shaped by the interaction of managerial and relational dimensions of teaching. The study concludes that fostering resilient learners requires not only effective classroom organization but also sustained social support from teachers, underscoring the importance of holistic pedagogical practices in contemporary education.